PENGARUH PENGGUNAAN LEMBAR KEGIATAN MAHASISWA (LKM) TERHADAP HASIL BELAJAR MATA KULIAH AKUNTANSI KEUANGAN MENENGAH I - Rochmawati Rochmawati; Irin Widayati; Kirwani Kirwani (Department of Accounting Education, Faculty of Teacher Training and Education Universitas, 2018)
This study aims to determine the effect of learning outcomes on students who use Contextual Student Activities Sheet (CSAS/LKM) with students who do not use CSAS in intermediate financial accounting I lesson. During this time the teaching and learning process in the classroom using only literature books. The research method in this study was an experiment using a t test analysis tool. the value of t count is 127,098 supported by a significance of 0.001 ≤ 0.005 for students of class 2016 who are divided into experimental and control classes. The results of the study showed that there are effects of student learning outcomes using CSAS/LKM on student learning outcomes.